Brown adipose tissue and glucose homeostasis – the link between climate change and the global rise in obesity and diabetes. (2nd January 2019) - Symonds, Michael E.; Farhat, Grace; Aldiss, Peter; Pope, Mark; Budge, Helen
ABSTRACT: There is increasing evidence that the global rise in temperature is contributing to the onset of diabetes, which could be mediated by a concomitant reduction in brown fat activity. Brown (and beige) fat are characterised as possessing a unique mitochondrial protein uncoupling protein (UCP)1 that when activated can rapidly generate large amounts of heat. Primary environmental stimuli of UCP1 include cold-exposure and diet, leading to increased activity of the sympathetic nervous system and large amounts of lipid and glucose being oxidised by brown fat. The exact contribution remains controversial, although recent studies indicate that the amount of brown and beige fat in adult humans has been greatly underestimated. We therefore review the potential mechanisms by which glucose could be utilised within brown and beige fat in adult humans and the extent to which these are sensitive to temperature and diet. This includes the potential contribution from the peridroplet and cytoplasmic mitochondrial sub-fractions recently identified in brown fat, and whether a proportion of glucose oxidation could be UCP1-independent. It is thus predicted that as new methods are developed to assess glucose metabolism by brown fat, a more accurate determination of the thermogenic and non-thermogenic functions could be feasible in humans.